Synthesis of stable isotopic data for human bone collagen: A study of the broad dietary patterns across ancient China. (February 2021) - Liu, Ruiliang; Pollard, Mark; Schulting, Rick; Rawson, Jessica; Liu, Cheng
Ancient China is one of the most important regions for the development of agriculture in human history, contributing the two key crops millet and rice. Meanwhile, it was closely connected to the wider Eurasian network, receiving wheat and barley from the West. Because of the large isotopic differences between C3 and C4 crops, we are able to track their changing importance in different regions of China and underlying connections to their cultural and environmental contexts. We take a 'big data' approach, assembling the stable isotopic measurements on over 2000 ancient human bones. This is the first comprehensive meta-analysis of ancient Chinese human stable carbon and nitrogen isotope results and creates a more efficient tool for scholars to establish a fuller picture of dietary practices in ancient China. By charting their spatial-temporal variation, we can show that the primary crop facilitating the rise of the early Chinese state in the Central Plains was millet, particularly during the Bronze Age. The dominance of millet (C4 ), from an isotopic viewpoint, offers an opportunity to investigate the major changes in dietary practice through the proxy of δ 13 C, as a result of shifts between millet and other major C3 crops (rice, wheat and barley). More importantly, millet is probably one of the earliest examples for the existing local system in the Central Plains within which other imported elements (e.g. wheat) have to fit. This pattern, which has also been repetitively discovered with bronze and iron technology in later periods, starts to characterise some intrinsic features of Chinese prehistory.